Effect of Earning Asset Quality and Non-Performing Loans on Capital Adequacy Level - Yusriadi Hala (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
This study aims to examine and analyze the effect of the quality of productive assets and non-performing loans on the level of capital adequacy. This research uses quantitative methods with an associative form. The research population is all banking companies listed on the Indonesia Stock Exchange for the period 2012-2019. Determination of the sample using purposive sampling technique focused on criteria for state-owned banks. Four companies were selected with a total sample size of 32 pieces analyzed using the multiple regression analysis models. The results showed that the variable of earning asset quality had a negative and significant effect on the level of capital adequacy of state-owned banks and non-performing loans had a negative and insignificant impact on the level of capital adequacy of state-owned banks. According to internal and external banking conditions, banking management manages to earn assets prudently by mitigating risks, as reflected in the significant growth in earnings values during the study period. Risk mitigation under operational principles is reflected in the NPL's small amount during the study period, indicating that the management has complied with the NPL value threshold required by the regulator. Professionally managed bank productive assets will lead to maximum profits and reduce unnecessary burdens so that the combination of the two will maintain the bank's capital adequacy level.